Revising a Model of Crime and Punishment - Arbiser, Ariel (Anais do Encontro de Teoria da Computação (ETC), 2019)
We study a model of society consisting of agents and a government interacting according to decisions regarding cost-effective punishment of crime. We evaluate different strategies for the government in order to reduce the criminal activity, considering degrees of honesty and a possible cost for monitoring and apprehension. We extend a previous model by introducing a contagion effect for the degrees of honesty, and study properties which may lead to a crime-free society, including a game-theoretic formulation.